Assessing informal healthcare providers' knowledge of diagnosis and treatment of malaria and diarrhea: evidence from urban informal settlements in Southeast Nigeria - Arize, Ifeyinwa; Ozughalu, Joy; Okechi, Bernard; Mbachu, Chinyere; Onwujekwe, Obinna; Ebenso, Bassey (Frontiers in Public Health, 2025)
BackgroundDespite the availability of effective interventions, malaria and diarrhea continue to be leading causes of disease burden in Nigeria. Informal healthcare providers (IHPs) account for a significant proportion of health service providers in urban slums and may pose a challenge to service quality if they are untrained and unregulated. This study assessed IHPs' knowledge of the diagnosis and treatment of malaria and diarrhea.MethodologyA cross-sectional quantitative study was conducted in eight urban informal settlements (slums) in southeast Nigeria. Data were collected from 235 informal health providers using an interviewer-administered questionnaire.ResultsThe mean overall knowledge scores for malaria and diarrhea were 5.2 (95% CI: 4.3–6.1) and 5.4 (95% CI: 4.1–6.7), respectively, among the different IHPs. However, private medicine vendors (PMVs) and traditional birth attendants (TBAs) showed higher knowledge of treating malaria and diarrhea. Having more than 8 years of formal education and receiving on-the-job training had a statistically significant effect on adequate knowledge of malaria and diarrhea treatment.ConclusionInstitutionalizing and strengthening service delivery through appropriate training and support for IHPs can improve the quality of health service delivery in urban slums.